2016
DOI: 10.1111/ped.12809
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between low vitamin D and rotaviral diarrhea?

Abstract: Low vitamin D is associated with rotaviral diarrhea. This is the first study in the literature to show this, and this result needs to be repeated in larger controlled clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…Found serum 25(OH)D <20 ng/ml associated with an odds ratio of 6.3 (95% CI, 3.6 to 10.9) for rotaviral diarrhea [116] ALRI, acute respiratory tract infection; cART, combination Antiretroviral Therapy; CHB, chronic hepatitis B; DENV-2, dengue virus-2; HIV-1, Human immunodeficiency virus 1; KSHV, Kaposi's sarcoma-associated herpesvirus; MDDCs, monocyte-derived dendritic cells; RSV, respiratory syncytial virus One way that CoVs injure the lung epithelial cells and facilitate pneumonia is through increased production of Th1-type cytokines as part of the innate immune response to viral infections, giving rise to the cytokine storm. A laboratory cell study reported that interferon γ is responsible for acute lung injury during the late phase of the SARS-CoV pathology [117].…”
Section: Rsvmentioning
confidence: 98%
“…Found serum 25(OH)D <20 ng/ml associated with an odds ratio of 6.3 (95% CI, 3.6 to 10.9) for rotaviral diarrhea [116] ALRI, acute respiratory tract infection; cART, combination Antiretroviral Therapy; CHB, chronic hepatitis B; DENV-2, dengue virus-2; HIV-1, Human immunodeficiency virus 1; KSHV, Kaposi's sarcoma-associated herpesvirus; MDDCs, monocyte-derived dendritic cells; RSV, respiratory syncytial virus One way that CoVs injure the lung epithelial cells and facilitate pneumonia is through increased production of Th1-type cytokines as part of the innate immune response to viral infections, giving rise to the cytokine storm. A laboratory cell study reported that interferon γ is responsible for acute lung injury during the late phase of the SARS-CoV pathology [117].…”
Section: Rsvmentioning
confidence: 98%
“…Rotaviral diarrhea Found serum 25(OH)D <20 ng/mL associated with an odds ratio of 6.3 (95% CI, 3.6 to 10.9) for rotaviral diarrhea [116] Note: acute respiratory tract infection (ALRI); combination Antiretroviral Therapy (cART); chronic hepatitis B (CHB); dengue virus-2 (DENV-2). Human immunodeficiency virus 1 (HIV-1); Kaposi's sarcoma-associated herpesvirus (KSHV); monocyte-derived dendritic cells (MDDCs); respiratory syncytial virus (RSV).…”
Section: H9n2 Influenzamentioning
confidence: 99%
“…In the present study enteropathogenic E. coli, Shigella sonnei, and Salmonella were .51 ng/mL). These mentioned studies confirmed that vitamin D deficiency is a predisposing factor for rotavirus diarrhea (24).…”
Section: Discussionmentioning
confidence: 61%
“…D concentrations and acute bacterial diarrhea. Studies in this area are contradictory (19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Bacterial agents are important causes of diarrhea in developing countries (1)(2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation